Pwede ba? - Ong, Denise Irene O. (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"Filipinos are truly fond of love stories, and I am no different. Having been raised believing that love should conquer all, I have always known that, one day, I shall also make a love story that will overcome all boundaries. This is a story about a straight guy who leads an average, everyday life who has never questioned anything until he meets a mysterious woman while waiting for a taxi. Deeply infatuated with her, he takes her up on her offer to watch her show at the bar where she works and discovers, to his disbelief, that she is actually a he! Now, he is suddenly confronted with a situation that will make him seek answers to the questions he has never asked himself before, and perhaps even open himself up to a whole new world of possibilities. Let's face it - we are all just human beings with the same pains, joys and desires, and who all just want to love and be loved in return. Tackling this story introduces not only a new twist to the formulaic love story that we have grown so accustomed to, but it also shows the real nature of human beings when faced with the dilemma of choosing to follow the rules of society has long ago set, or to deviate and create his own set of rules, risking all to find true happiness in the process. This is evident of the theory of Dramatism that Kenneth Burke has surmised, saying that life is a drama, which involves conflict and division that threatens some sort of existing order. What results from this conflict, however, us that the drama invites or discourages specific action from its actors. The sudden discovery by Ben that Sam is a transvestite threatens the norms of Ben's "straight" world, but it also spurs him into action - choosing between rejecting the discover, accepting it, or creating a compromise that will allow him to learn more about himself than society would have him to."
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman